Cycling as a Part of Recreation: An Awareness-Exploring Study - Merve Uca,; Leyla Alizadehebadi,; Sevim Handan Yılmaz, (Journal of Educational Issues, 2024)
This study aimed to explore the awareness among individuals engaged in recreational cycling about the benefits of cycling. The study consists of 66 participants in the age group of 18-30 who are interested in recreational cycling in the province of Sakarya. The “Recreation Awareness Scale” developed by Ekinci and Özdilek (2019) was used as a data collection tool in the study. In the study, skewness and kurtosis (kurtosis) were evaluated to ensure the normal distribution of the data in addition to descriptive statistical methods such as percentage and frequency. As a result, we found the data to be normally distributed and, thus, utilized the parametric tests. Accordingly, the groups were compared using a t-test and an analysis of variance (ANOVA). In addition, we performed a Tukey test to find out the group(s) as the source of difference. Then, Pearson’s correlation analysis was performed to see the association between two continuous variables. The results revealed that the participants did not differ significantly on pleasure/entertainment, social/achievement, and self-development subscales by gender. Yet, the mean scores of the participants differed significantly on the social/achievement and self-development subscales by educational attainment. The post hoc test suggested that those having a high school degree got significantly higher scores on the social/achievement subscale than the participant with an associate degree. Moreover, the high school graduates obtained higher scores on the self-development subscale than those with a secondary school, associate, and undergraduate degree. Considering the relationship between recreation awareness and age, the Pearson’s correlation test revealed significant positive relationships between age and the participants’ scores on the social/achievement and self-development subscales. Yet, we could not find a significant relationship between age and the pleasure/entertainment subscale.